Microevolutionary differentiation of cereal tetraploid species by formation of recombinant genomes - N. I. Dubovets; Ye. A. Sycheva (Вавиловский журнал генетики и селекции, 2016)
The process of microevolutionary differentiation of cereals by formation of recombinant genomes was studied in dynamics (F6–F17) with tetraploid wheat-rye amphidiploids as examples. Evidence that joint growing of tetra ploid amphidiploids having a common (pivotal) genome in their composition and differing in secondary (differential) genomes leads to their hybridization with high probability has been found. The forms developed are characterized by a very wide range of variability caused by different combinations of chromosomes and chromosome segments in differential genomes yet maintain the same structure of the pivotal genome. Intergenomic recombinations at the level of intact chromosomes were characteristic of homeologous groups with a high rate of stabili zation of the chromosomal composition, and recombinations at the level of chromosomal segments, of groups with a low stabilization rate, where heterologous chromosome pairs remained preserved for a long time. Dominance of regulatory genetic systems of the pivotal genome provides a high pairing level of homeologues from heterologous pairs in meiosis followed by intergenomic recombinations at the level of chromosome segments. Experimen tal data suggest that newly developed tetraploid forms interbreed easily forming a single hybrid zone, where permanent redistribution of genetic material of differential genomes and further range expansion of genotypic variability available to selection take place during alternation of generations whereby such a zone becomes a poten tial centre of speciation. Subsequent adaptive radiation of hybrid material in an ecologically separated environment occurs by selection of forms with different variants of the recombinant genome in various ecological niches.